EXERCISE ENHANCING CALCIUM ABSORPTION MECHANISM - **, Muliani (Medicina; Vol 43 No 2 (2012): Mei 2012, 2013)
Calcium has important role in many biological processes therefore calcium homeostasis should be maintained. Imbalance in calcium homeostasis would affects the bone metabolism, neuromuscular function, blood coagulation, cell proliferation and signal transduction. Homeostasis of calcium is maintained by three major organs: gastrointestinal tract, bone and kidney. Intestinal calcium absorption is the sole mechanism to supply calcium to the body. Calcium absorption controlled by calcitropic hormones (1,25-dihydroxycholecalciferolvitamin D3 (1,25-(OH)2D3) and parathyroid hormone (PTH). Exercise enhancing calcium absorption through transcellular and paracellular calcium transport by increasing the calcium transporter genes .
Keywords: calcium, exercise, calcium transport